Geological, geomorphological and pedological studies for the rehabilitation of an degraded area by mining industry (2008)
The present work describes the integration between geology, geomorphology and soils rescarch for the rehabilitation of a degraded area degraded by artisan mining, located in the nothwest of the Minas Gerais  State, Brazil. For the more shattered areas, the rehabilitation may be developed by means of the increase of the soils and the vegetable cover. In the Lateritic Slope, the ocurrence of latosols enables the utilization on the area for cultures and pastures.